Sistem Pendukung keputusan Pemilihan Bibit Cabai Unggul Berbasis Web Menggunakan Metode Profile Matching di Kab. Langkat Sumut - Pratama, Angga; Hardiansyah, Muhammad; Muthmainnah, Muthmainnah (Jurnal Ilmiah SINUS, 2024)
Chili plants are one of the leafy foods with excellent business prospects. Because of their capacity for development, chili plants are a quality commodity and a significant part of Indonesian horticulture. Because of the strong demand for chili both domestically and internationally, chili becomes a potential item. Farmers often find difficulty to determine the chili seeds. The difficulty of determining good chili seeds often causes some farmers failed to harvest and experience considerable losses. Therefore identifying chili seeds is one of the right solutions compared to buying chili seeds at a fairly high price. Naturally, the process of choosing the best chili seeds is based on pre-established standards. In this study, the profile matching method was used to create a decision support system for selecting the best chili seeds. PHP and MySQL were used to create this system. The goal of developing this method is to facilitate farmers' selection of premium chili seeds. In the province of North Sumatera, Langkat Regency agriculture department provided data for this study, along with information from resource people, books, and other literary works. Based on predetermined criteria, the research produced a rating of the best chili seeds, from highest value to lowest.